ANALISIS PENCEMARAN UDARA AKIBAT PABRIK ASPAL BERDASARKAN PERATURAN PEMERINTAH NOMOR 41 TAHUN 1999 TENTANG PENGENDALIAN PENCEMARAN UDARA - Nurhaedah Hasan, Ibrahim Fattah, Risna (FAKULTAS HUKUM UM PAREPARE, 2020)
This research is a research that aims to determine the extent of the analysis of air pollutiondue to asphalt factories based on Government Regulation No. 41/1999 concerning air pollutioncontrol, as well as knowing the role of laws and regulations on air pollution. This research isnormative research. Normative research is research conducted through library research in findingtheoretical data sources that are useful for solving problems. The legal materials used based on theresearch approach are primary legal materials. Primary legal materials are legal materials that havebinding strength. such as laws, government regulations and Ministerial regulations. As well astertiary legal materials such as legal dictionaries, internet, and large Indonesian dictionaries. Whilethe data analysis used is to collect library data using a qualitative-descriptive approach. The resultsof the study can be concluded that the first rules regarding air pollution are contained in the field ofregulations based on the constitution to the ministerial regulations, among others, the 1945Constitution (article 33), Law NO. 32 of 2009 concerning Protection and management of theenvironment, Law NO.3 of 2014 concerning Industry, Government Regulation of the Republic ofIndonesia NO.41 of 1999 concerning Air Pollution Control, Government Regulation NO.107 of 2015concerning Industrial Permits, Government Regulation No. 27 of 2012 concerning EnvironmentalPermits, Ministerial Decree NO. 45 of 1997 concerning Air Pollutant Standard Index, Regulation ofthe minister of state for the environment No 12 of 2010 concerning the implementation of air pollutioncontrol in the area of the minister of state for the environment. The two supervision carried out by thegovernment on air pollution at the asphalt factory, among others; directing or recommendingimprovements, suggesting that waste is suppressed; and optimizing work to achieve plan goals. Theresearcher recommends that the government increase its supervision of the asphalt plant again inorder to create an environmentally friendly asphalt plant.